rozwiąż równania wielomnianowe​



Rozwiąż Równania Wielomnianowe class=

Odpowiedź :

[tex]e) 2x^{3} -6x^{2} +x-3=x(2x^{2} -6x+1-3)=x(2x^{2} -6x-2)\\x_{1} =0\\[/tex]

Δ=36+16=52

√Δ=√52=2

[tex]x_{2} =\frac{6+2\sqrt{13} }{4} =\frac{3+2\sqrt{13} }{2}\\x_{3} =\frac{6-2\sqrt{13} }{4} =\frac{3-2\sqrt{13} }{2}\\[/tex]

[tex]f) 3x^{4} +6x^{3}-8x^{2}-2x-3=3x^{4} +9x^{3}+x^{2} +3x-3x^{3}-9x^{2} -x-3=\\=x(3x^{3}+9x^{2} +x+3)-1(3x^{3} +9x^{2} +x+3)=(x-1)(3x^{3}+9x^{2} +x+3)=\\=(x-1)(3(x^{3}+3x^{2})+x+3)=(x-1)(3(x+3)*x^{2} +1(x+3))=\\=(x-1)(x+3)(3x^{2} +1)[/tex]

[tex]x_{1} =1\\x_{2} =-3\\3x^{2} =-1\\x^{2} =-\frac{1}{3} sprzeczne[/tex]